Growth and Electronic Transport Property of Layered BiOCl Microplates. Issue 12 (14th July 2015) - Zhang, Yangwei; Xu, Xianghan; Xing, Ying; Wang, Huichao; Fu, Hailong; Lin, Xi; Wang, Jian
<x xml:space="preserve">Abstract</x> Single crystalline BiOCl microplates (MPs) are successfully fabricated with controllable sizes via a simple hydrothermal method. The resistivity of BiOCl MPs as a function of temperature shows semiconducting behavior in the high temperature region but shows a drop below 8.52 K, which indicates a transition from insulating‐like to superconducting‐like behavior in the low temperature regime.